Efeito do nível e da época de desfolha artificial sobre os componentes de produtividade de cultivares de algodoeiro - Michelotto, Marcos Doniseti; Galli, Juliana Altafin; Crosariol Netto, Jacob [UNESP]; Pirotta, Melina Zacarelli [UNESP]; Busoli, Antonio Carlos [UNESP] (My University, 2013)
The periodic substitution of cotton cultivars for the farms can modify the levels of economic damages and control of pests, compromising the success in pest control. The objective of this work was to evaluate the effect of simulated defoliation levels in cotton cultivars actually used. The assay was carried out in experimental area of the Polo Apta Centro Norte, in Pindorama, São Paulo state. There were evaluated four defoliations levels (0%, 36.8%, 62.1% e 100%), done at a unique operation, in tree times (30, 60 and 90 days after plant emergence) and four cotton cultivars (IAC-25, DeltaOpal, Fibermax 966 and Fibermax 993). The defoliation was done with a scissor simulating the caterpillar damage. Evaluations included the number of open bolls, weight of one boll and 100 seeds, fiber percentage and productivity (kg ha-1). The defoliation negatively affected all components of agronomic traits, with the exception of percentage of fiber. The most damaging levels were 62.1 and 100% removal of the leaf blade. The period of higher susceptibility to defoliation occurs from 30 to 60 days after plant emergence.
Effect of level and time defoliation on the agronomic traits of cotton cultivars
Keywords: Cotton leafworm; Gossypium hirsutum; Leaf area; Simulated damage